Evaluation of the potential anti-alcoholism activity of chitosan grafted with gallic acid. Issue 1 (January 2021) - Lu, S T; Yu, J Y; Hu, Z; Zhang, L Y; Huang, D J; Liao, M N
Abstract: In order to broaden the application of chitosan (CS) in the anti-alcoholism, gallic acid (GA) was grafted onto the CS molecular chain by 1-(3-dimethylaminopropyl)-3-ethyl carbodiimide hydrochloride (EDC)-mediated coupling, and the structure of gallic acid grafted chitosan (CS-GA) was characterized by using UV-Vis spectroscopy (UV-Vis) and Fourier transform infrared spectroscopy (FTIR). The potential anti-alcoholism activity of CS-GA was preliminarily evaluated with ethanol adsorption rate and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging rate. The results showed that GA was grafted onto the CS successfully and CS-GA was obtained. CS-GA could adsorb a large amount of alcohol and reach a peak within 15 min after contact with alcohol in vitro. The DPPH radical scavenging ability of CS-GA was 57.5%, which was 2.4 times of CS. In summary, CS-GA had vigorous potential anti-alcoholism activity and is expected to be developed as a promising antidote.